دابەشبوونی جوگرافی پەرستگا و مەزارگە ئاینییەکانی ئێزیدیی و مەسیحییەکان لە هەرێمی کوردستان - ڕشـید, پ.ی.د. شـیروان عـمر; مـحمد, خوێندکاری ماستەر: عـدنان عـلی (Sulaimani Journal for Humanities, 2023)
This research entitled (Geographical Distribution of Yazidi and Christian Religious Temples and Shrines in the Kurdistan Region) aims to present the distribution of Yazidi and Christian temples and shrines and geographical location and religious tourists, which is considered an important aspect of religious tourism The aim of the study is the importance of these religious centers for religious tourism, because there are many temples and shrines in the world only in these areas, including (Lalsh Temple, Ankawa, Mary Azra Church, etc.). It also shows the level of various services, for this purpose relies on various methods, including methods (descriptive, analytical), an attempt to show and further introduce these religious areas, as it appears that there are a large number of shrines and religious temples It provides economic and social security In order to use it for the development of religious tourism, the study is divided into three themes, in addition to conclusions and recommendations.
Keywords: کلیلی وشەکان مەزارگە و پەرستگا ئاینییەکان ئێزیدییەکان مەسیحییەکان هەرێمی کوردستان